RESPON PEMBERIAN BEBERAPA DOSIS PUPUK FOSFOR TERHADAP PERTUMBUHAN SEMAI AKASIA (Acacia mangium Willd.) DAN KETERSEDIAAN FOSFORDI TANAH - Faizin, Nur; Yoza, Defri; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Acacia mangium Willd. classified as plants that require nutrients are complete and available or Nutrient demanding crop, althought for grow and evolve requires a lot of nutrients that one of them is the phosphorus element. Phosphorusis needed absorption of nutrientsb by increasing the number of nodules on the roots so as to increase plant growth. The fertilization is o.0ne way that can be done to fulfill the availability of soil nutrients that plants need. The purpose of this research is to determine the effect of phosphorus fertilizer application on acacia seedlings in topsoil medium, determine the best dose to the growth of seedlings of acacia and check the availability of phosphorus in the soil at this seedling. This research uses a completely randomize design method which consist of 4 treatments and 10 replications. T0 = without phosphorus fertilizer; T1 = 20 g/polybag ; T2= 25 g/polybag ; T3 = 30 g/polybag ;.The resultsof this research indicates thatthe phosphorus fertilizer with 25 g / polybag dose on top soil medium is the best treatment in the parameter of observations, the high increasing (9.36 cm), the diameter increasing (1.19 mm)for seedling Acacia mangium Willd. in topsoil medium. GivingÂ of phosphorus fertilizer can increase soil pH (4.56), P-bray (527.66 mg / kg) and P-total (7000.1 mg / kg) the availability increasing of phosphorus in the soil for growth seedlings Acacia mangium Willd. Keyword :Fosfor fertilizer, Growth, Seedling, Accacia mangium Willd.